In vitro comparative study of two Arundo donax L. ecotypes’ selenium tolerance - Domokos-Szabolcsy, É.; Abdalla, N.; Alshaal, T.; Sztrik, A.; Márton, L.; El-Ramady, H. (International Journal of Horticultural Science, 2014)
Selenium tolerance of two somatic embryo-derived Arundo donax L. ecotypes (Blossom, 20SZ) were compared in in vitro culture. Sodium-selenate (1 – 100 mg L-1) as known the most phytoavailable selenium form and the less studied red elemental nanoselenium (100 mg L-1) were applied as selenium treatments. Basis on the results Blossom ecotype seemed to be more sensitive to the sodium-selenate than 20SZ. Inhibiting effect of selenate was effectuated above 10 mg L-1 in case of Blossom, which was manifested in decreased survival rate and growing parameters. Contrast to this 20SZ could tolerate the selenate ≤ 20 mg L-1 without any toxic symptoms. Lower selenate tolerance of Blossom could be explained with higher selenium accumulation. Both of two ecotypes could also uptake and accumulate the red elemental nanoselenium however in much less extent compared to selenate.